THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK STRESS ON EMPLOYEE PERFORMANCE IN PT SETIA SEJAHTERA PERKASA - Priyotomo, Hadi (BAIK Publishers, 2024)
The purpose of this study was to determine the effect of organizational culture and job stress on employee performance at PT Setia Sejahtera Perkasa. The research method used in this research is descriptive with a quantitative approach. The population was 49 people. The sampling technique using saturated samples so that the number of samples in this study was 49 respondents. Data analysis techniques using multiple regression. The results showed that: (1) There is a positive and significant influence of organizational culture variables on the performance of employees of PT Setia Sejahtera Perkasa with a tcount > ttable value, namely 7.315 > 2.013 and a significance value = 0.000 which is below 0.05. (2) There is a positive and significant effect of work stress variables on the performance of employees of PT Setia Sejahtera Perkasa with a tcount > ttable value, namely 8.151 > 2.013 and a significance value = 0.000 which is below 0.05. (3) There is a positive and significant influence of organizational culture and work stress variables on the performance of employees of PT Setia Sejahtera Perkasa with the value of Fcount > Ftable value, namely 40.302 > 3.20 and a significance value = 0.000 which is below 0.05.